A Versatile Assay for High-Throughput Gene Expression Profiling on Universal Array Matrices - Fan, Jian-Bing; Yeakley, Joanne M.; Bibikova, Marina; Chudin, Eugene; Wickham, Eliza; Chen, Jing; Doucet, Dennis; Rigault, Philippe; Zhang, Baohong; Shen, Richard; McBride, Celeste; Li, Hai-Ri; et al. (Genome Research, 2004)
We report a flexible, sensitive, and quantitative gene-expression profiling system for assaying more than 400 genes, with three probes per gene, for 96 samples in parallel. The cDNA-mediated annealing, selection, extension and ligation (DASL) assay targets specific transcripts, using oligonucleotides containing unique address sequences that can hybridize to universal arrays. Cell-specific gene expression profiles were obtained using this assay for hormone-treated cell lines and laser-capture microdissected cancer tissues. Gene expression profiles derived from this assay were consistent with those determined by qRT-PCR. The DASL assay has been automated for use with a bead-based 96-array matrix system. The combined high-throughput assay and readout system is accurate and efficient, and can cost-effectively profile the expression of hundreds of genes in thousands of samples.